2008
DOI: 10.1074/mcp.m800052-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

A Proteomics Approach for Identification of Single Strand DNA-binding Proteins Involved in Transcriptional Regulation of Mouse μ Opioid Receptor Gene

Abstract: The pharmacological actions of morphine and morphinelike drugs such as heroin are mediated primarily through the opioid receptor. Previously a single strand DNA element of the mouse opioid receptor gene (Oprm1) proximal promoter was found to be important for regulating Oprm1 in neuronal cells. To identify proteins binding to the single strand DNA element as potential regulators for Oprm1, affinity column chromatography with the single strand DNA element was performed using neuroblastoma NS20Y cells followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…A previous study indicated that the mouse PPy/u motif, a single stranded cis-regulatory element, and PCBP1, an α-CP1 trans-acting protein, are important for MOR PP activity (15). The present study demonstrated that α-CP1 enhanced MOR promoter activity and endogenous MOR transcription via α-CP1 binding to the ssDNA element (17). To the best of our knowledge, this is the first study to solubilize, fold, purify and produce a functionally active α-CP1 for DNA EMSA analysis using the E. coli protein expression system.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…A previous study indicated that the mouse PPy/u motif, a single stranded cis-regulatory element, and PCBP1, an α-CP1 trans-acting protein, are important for MOR PP activity (15). The present study demonstrated that α-CP1 enhanced MOR promoter activity and endogenous MOR transcription via α-CP1 binding to the ssDNA element (17). To the best of our knowledge, this is the first study to solubilize, fold, purify and produce a functionally active α-CP1 for DNA EMSA analysis using the E. coli protein expression system.…”
Section: Discussionsupporting
confidence: 48%
“…The proximal core promoter of the Differential regulation of mouse and human Mu opioid receptor gene depends on the single stranded DNA structure of its promoter and α-complex protein 1 mMOR gene contains the polypyrimidine/polypurine (PPy/u) region, and the PP of the human MOR (hMOR) gene contains a similar PPy/u region that is located nearby at transcription initiation site (14,15). The PPy/u region of the mMOR gene promoter strongly activates the MOR gene and contains a 26-bp CT-rich region with overlapping single-and double-stranded DNA sequences, and multiple binding sites for Sp1, Sp3 and single-stranded binding proteins (16,17). Regulation of hMOR gene expression in neuronal cells is not well understood compared with mMOR gene regulation.…”
Section: Introductionmentioning
confidence: 99%
“…The l opioid receptor (MOR) plays roles in morphine-induced analgesia, tolerance, and dependence, as indicated by pharmacological studies and analyses of MOR gene knockout mice [3,4]. MOR expression is regulated by multiple mechanisms, including transcriptional [5][6][7][8][9][10][11][12] and posttranscriptional events [13][14][15]. However, the translational control of the MOR gene has not been well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…PCBP1 expression plasmid (myc-tagged pcDNA4-PCBP1, also called pcDNA4-αCP1) was described previously (Choi et al, 2008). Mutations of PCBP1 for phosphorylation, NES, and NLS sites in pcDNA4-PCBP1 were generated by PCR site-directed mutagenesis using high-fidelity Pfu DNA polymerase according to the manufacturer's protocol (Quikchange, Stratagene) with the respective PCR primer sets (Table 1).…”
Section: Methodsmentioning
confidence: 99%